Community Participatory Communication Lampion Village In Maintaining Yogyakarta Cultural Identity - Annisa Luthfah Shafira; Dasrun Hidayat (Kanal: Jurnal Ilmu Komunikasi, 2022)
This study aims to determine how the role of participatory communication developed by the people of Kampung Lampion in maintaining their cultural identity, namely the city branding of Jogja Istimewa. This study also uses a qualitative descriptive analysis method that describes and examines more deeply the community's participatory communication in maintaining the unique cultural identity of Jogja to understand what the role of the Kampung Lampion community is in supporting and strengthening the identity of Yogyakarta. The results showed that the Kampung Lampion community participated and fully supported the branding through the implementation and preservation of Kampung Lampion Code 18. The form of participatory communication for the Kampung Lampion Code 18 community consisted of heteroglossia characterized by the diversity of age and profession of the community, the average age of which was 30 to 70 years. Meanwhile, the diversity of community professions consists of housewives, traders, laborers, and civil servants (PNS). Dialogic is a form of communication where there is an interaction transaction between the community and the regional head in deliberation. Polyphonic participatory communication occurs when there is freedom of expression in deliberation conducted by the village of lantern code 18. Carnival participatory communication is marked by community compliance when the government holds activities or programs. Where the community enthusiastically followed directions from the government to join in enlivening the activity.